Food Insecurity Exists among College Students at a Midsized University in Utah. Issue 1 (2nd January 2023) - Savoie-Roskos, Mateja R.; Harrison, Caleb; Coombs, Casey; Hendrickson, Jackie; Hawes, Rachel; Barney, Madison; Doxey, Jamie; LeBlanc, Heidi
ABSTRACT: This study examined the prevalence of and identified characteristics associated with food insecurity among students at a midsized university in Utah. A cross-sectional survey of university students (n = 952) was conducted. Nearly 33% (n = 302) of students experienced food insecurity in the past 30 days. A weak, yet significant association was found between food security status and gender, marital status, year in school, employment, use of food assistance, use of other assistance, use of the on-campus food pantry, and parental education level. There is a need for increased awareness of on-campus programs and policies aimed at reducing food insecurity among college students.